(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The experiment was conducted in one of the private fields north of Basra for the growing season 2022-2023. To study the effect of the hormone brosnolide, soil improver polymer and different irrigation periods on some growth and yield characteristics of okra plant. The experiment included a study of the effect of three factors: the hormone brosnolide at three concentrations (0, 3, 6) mg l and the polymer hydrogel at concentrations (0, 50, 100) g m² soil, and irrigation periods (3, 6) days, and their double and triple interactions. The experiment was designed according to (R.C.B.D.) Complete Blocks Design Randomized with three replicates for each treatment, and the least significant difference test was adopted at the probability level (0.05). The results showed that treating plants with the hormone brosnolide led to a significant increase in all studied traits, as the concentration exceeded 6 mg l in each plant height, fresh weight, dry weight, pod weight, single plant yield, and total yield. The effect of the soil-enhancing polymer led to a significant increase in all the studied traits at a concentration of 100 g m² soil, except for the yield of one plant, as the treated plants excelled at a concentration of 50 g m² soil. Irrigation periods of 3 days significantly affected all the studied traits. The binary interactions also showed a significant effect on all the traits studied. The triple interactions led to a significant increase in all the studied traits at a hormone concentration of 6 mg l and polymer at a concentration of 100 g m² soil and an irrigation period of 3 days compared to the control treatment and an irrigation period of 6 days.